THE CONTEMPORARY AND THE POSTHUMOUS - Behler, Ernst (Surfaces, 1994)
Culture humanism are problematic notions that cannot be reduced to a singular meaning and that are often in conflict with one another. This essay examines these notions historically, in early German Romanticism and Nietzsche, with discussions of Novalis and the Schlegels, among others, and concludes with theoretical reflections on these themes and their contemporary significance.